化简(sin(2π-a)tan(π+a))⼀(cos(π-a)tan(3π-a)tan(-π-a))=

2025-02-26 01:54:46
推荐回答(5个)
回答1:

sin(2π-a)=-sina,tan(π+a)=-tana,cos(π-a)=-cosa,tan(3π-a)=-tana,tan(-π-a))=-tana,
所以原式=-sina*tana/cosa*tana*tana=-1

回答2:

(sin(2π-a)tan(π+a))/(cos(π-a)tan(3π-a)tan(-π-a))
=(-sinatana)/(-cosatan²a)
=1

回答3:

解: sin(π-a)tan(2π-a)cos(-a+3π/2)/tan(-π-a)cos(-π-a) =[sinatan(-a)(-sina)]/[(-tana)(-cosa)] =[sina(-tana)(-sina)

回答4:

等于1

回答5:

原式=(-sina)tana/[(-cosa)(-tana)(-tana)]
=sina/(cosatana)
=sina/(cosa*sina/cosa)
=1